Monomethyl lithospermate alleviates ischemic stroke injury in middle cerebral artery occlusion mice in vivo and protects oxygen glucose deprivation/reoxygenation induced SHSY-5Y cells in vitro via activation of PI3K/Akt signaling - Yang, Fang; Chen, Ze-Ran; Yang, Xu-Hong; Xu, Yue; Ran, Ning-Jing; Liu, Mei-Jun; Jin, Shuo-Guo; Jia, Hua-Nan; Zhang, Yang (Frontiers in Pharmacology, 2022)
Stroke is a fatal neurological disease, which seriously threatens human health and life. Ischemic stroke (IS) is the most common type of stroke in clinic. Its pathogenesis is very complex, mainly caused by nerve damage caused by brain blood supply disorder. Previous studies have confirmed that natural products play important roles in improving neurological disorders. Furthermore, our previous results also suggested that Shenxiong Tongmai granule, a clinically used herbal medicines’ prescription, has a good ameliorating effect on IS. In the present study, we found that Monomethyl lithospermate (MOL), a constituent of Shenxiong Tongmai granule, significantly improved the neurological damage in middle cerebral artery occlusion (MCAO) rats. MOL can significantly improve the neurological deficit score of MCAO rats, and improve the damage of hippocampal neurons caused by ischemia-reperfusion (IR). At the same time, we also found that MOL could reduce the level of oxidative stress in the brain tissues of MCAO rats. Furthermore, the oxygen and glucose deprivation / Reoxygenation (OGD/R)-induced SHSY-5Y cell model was established in vitro to investigate the pharmacological activity and molecular mechanisms of MOL in improving the nerve injury of IS rats. The results showed that MOL could increase the cell viability of SHSY-5Y cells, inhibit the mitochondrial membrane potential (MMOP) collapse and suppress apoptosis. In addition, MOL also ameliorated the elevated oxidative stress level caused by OGR/R treatment in SHSY-5Y cells. Further mechanistic studies showed that MOL could activate the PI3K/AKT pathway via promoting the phosphorylation of PI3K and AKT in MCAO rats and OGR/R-induced SHSY-5Y cells, which could be partially blocked by addition of PI3K/AKT pathway inhibitor of LY294002. Taken together, our current study suggested that MOL exerts a protective effect against neural damage caused by IS in vivo and in vitro by activating the PI3K/AKT pathway.